Moral Perspective of Emotions in Formal Education Contexts - Mujica Johnson, Felipe Nicolás (2019)
This essay responds to a critical analysis of emotional education, considering that emotions in education are being addressed from a therapeutic perspective based on the hedonistic tradition of psychology, which does not correspond to a pedagogical knowledge, especially when the philosophical foundations of education are not considered. Taking into account this criticism, this essay is generated which aims to analyze the moral value of emotions. It is identified that the same emotion can have a positive or negative value in relation to the meaning of the educational goal. It is concluded that it is not possible to standardize the pedagogical-moral value of emotions since it responds to a qualitative analysis of the pedagogical situation.